Biodiesel production from castor oil using heterogeneous Ni doped ZnO nanocatalyst. (February 2018) - Baskar, G.; Aberna Ebenezer Selvakumari, I.; Aiswarya, R.
Graphical abstract: Highlights: Ni doped ZnO nanocatalyst was found to be effective for production of biodiesel using castor oil. The size and structure of nanocatalyst was confirmed by AFM and XRD. The transesterification process parameters were optimized by both conventional and RSM methods. The castor oil was successfully transesterified to biodiesel with the yield of 95.20%. Abstract: In the present study, castor oil with high free fatty acid was used for biodiesel production using heterogeneous Ni doped ZnO nanocatalyst. Ni doped ZnO nanocomposite calcinated at 800 °C has shown better catalytic activity. Process parameters on heterogeneous catalysis of castor oil into biodiesel were optimized using conventional and Response Surface Methodology (RSM). RSM was found more accurate in estimating the optimum conditions with higher biodiesel yield (95.20%). The optimum conditions for transesterification was found to be oil to methanol molar ratio of 1:8, catalyst loading 11% (w/w), reaction temperature of 55 °C for 60 min of reaction time by response surface method. The reusability studies showed that the nanocatalyst can be reused efficiently for 3 cycles.